2012
DOI: 10.1139/w11-140
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in arbuscular mycorrhizal fungi compatibility supports the selection of durum wheat genotypes for enhancing soil ecological services and cropping systems in Canada

Abstract: Crop nutrient- and water-use efficiency could be improved by using crop varieties highly compatible with arbuscular mycorrhizal fungi (AMF). Two greenhouse experiments demonstrated the presence of genetic variability for this trait in modern durum wheat ( Triticum turgidum L. var. durum Desf.) germplasm. Among the five cultivars tested, 'AC Morse' had consistently low levels of AM root colonization and DT710 had consistently high levels of AM root colonization, whereas 'Commander', which had the highest colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 48 publications
(61 reference statements)
6
46
3
1
Order By: Relevance
“…One objective of this study was to identify genotypic differences in wheat with regard to root colonization by mycorrhizal fungi and to obtain information on the genetics of mycorrhiza symbiosis. Previous studies, in which smaller sets of wheat genotypes were analyzed, have hinted at the presence of genotypic differences concerning root colonization (Kapulnik & Kushnir, ; Hetrick et al ., ; Zhu et al ., ; Singh et al ., ). Root colonization by mycorrhizal fungi was in the range 29–48% in diploid and hexaploid wheats, 18–71% in modern wheat cultivars, 6–71% in landraces originated from Asia and America, and 16–37% in Australian cultivars or modern durum wheat cultivars ( Triticum turgidum var.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One objective of this study was to identify genotypic differences in wheat with regard to root colonization by mycorrhizal fungi and to obtain information on the genetics of mycorrhiza symbiosis. Previous studies, in which smaller sets of wheat genotypes were analyzed, have hinted at the presence of genotypic differences concerning root colonization (Kapulnik & Kushnir, ; Hetrick et al ., ; Zhu et al ., ; Singh et al ., ). Root colonization by mycorrhizal fungi was in the range 29–48% in diploid and hexaploid wheats, 18–71% in modern wheat cultivars, 6–71% in landraces originated from Asia and America, and 16–37% in Australian cultivars or modern durum wheat cultivars ( Triticum turgidum var.…”
Section: Discussionmentioning
confidence: 97%
“…durum Desf.) (Kapulnik & Kushnir, ; Hetrick et al ., ; Zhu et al ., ; Singh et al ., ). The results of this study (24–56% root colonization) are in accordance with these data.…”
Section: Discussionmentioning
confidence: 97%
“…Large differences in responsiveness were also reported among plant species and varieties, for instance, in wheat (Singh et al, 2012) and maize . Hetrick et al (1992) reported a loss of response to colonization in modern varieties of wheat, compared with older varieties, ancestors, and landraces.…”
Section: Genetic Traits Of Plantemicroorganisms Relationships Involvementioning
confidence: 91%
“…Recent scientific findings have additionally shown that mycorrhizal symbiosis may vary depending on the crop cultivar, e.g. durum wheat (Singh, Hamel, DePauw, & Knox, 2012), maize (An, Kobayashi, Enoki, Sonobe, Muraki, Karasawa, & Ezawa, 2010), and tomato (Steinkellner, HageAhmed, García-Garrido, Illana, Ocampo, & Vierheilig, 2012). More intriguing are the recent findings that modern genotypes could be less intensively colonized by AMF than ancestral ones (Lehmann, Barto, Powell, & Rillig, 2012).…”
Section: Soil Fertilitymentioning
confidence: 99%